Ozone profile measurements of McMurdo Station, Antarctica, during the spring of 1987 - Hofmann, D. J.; Harder, J. W.; Rosen, J. M.; Hereford, J. V.; Carpenter, J. R. (1989)
Ozone and temperature profiles were measured in 50 balloon flights at McMurdo Station (78 deg S) during the spring of 1987. Compared to similar data obtained in 1986, stratospheric temperatures were lower and the spring time Antarctic ozone reduction was greater in magnitude, extended to higher altitude, and proceeded at a higher rate in 1987. Ozone partial pressures reached values as low as 3 nbar (as compared to about 10 nbar in 1986) in the 16- to 18-km region in early and late October, down from about 150 nbar in late August. These low values suggest essentially complete removal of ozone in this region. The upper boundary of the depletion region was observed to be 2-3 km higher than in 1986, extending to altitudes as high as 24 km in mid-September. When averaged over September, the ozone mixing ratio at 18 km decayed with a half-life of only 12.4 days, as compared to about 28 days in 1986. Adiabatic vertical motions over 1- to 2-km intervals between 12 and 20 km with consequent ozone reductions were observed in association with the formation of nacreous clouds, indicating these to be rare events on a local scale probably associated with mountain lee waves.